Phase I study of combined pegylated liposomal doxorubicin with protracted daily topotecan for ovarian cancer - Mirchandani, Deepu; Hochster, Howard; Hamilton, Anne; Liebes, Leonard; Yee, Herman; Curtin, John P; Lee, Sang; Sorich, Joan; Dellenbaugh, Cornelia; Muggia, Franco M (Clinical cancer research, 2005)
To determine the maximum tolerated dose and dose-limiting toxicity of Doxil with low-dose continuous infusion topotecan and subsequently with low-dose oral topotecan. Other specific aims were preliminary assessment of activity in advanced ovarian and tubal malignancies, pharmacokinetics of oral topotecan, and correlation of response with topoisomerase I and II expression in tumors. Eligible patients had histopathologically documented advanced cancers beyond standard therapy, performance status <2, and adequate organ functions. Doxil (30-40 mg/m2 i.v.) was given on day 1, with topotecan either oral topotecan 0.4 mg/m2 bid for 14 days or continuous infusion topotecan (0.3-0.4 mg/m2/d) for 14 to 21 days, in 28-day cycles. Fifty-seven patients, 23 with epithelial ovarian or tubal cancers were enrolled. Plasma levels of lactone form of topotecan were determined on patients receiving oral topotecan. Grade 4 neutropenia and thrombocytopenia and grade 3 diarrhea were dose-limiting toxicities at the highest dose levels explored. Doxil (40 mg/m2/day 1) and continuous infusion topotecan at 0.4 mg/m2/days 1 to 14 could be safely given and is the recommended phase II dose. Oral topotecan was limited by low and erratic plasma topotecan levels and frequent gastrointestinal toxicity. Particularly long partial responses and stable disease were observed in patients with epithelial ovarian or tubal cancers. Clinical benefit (objective responses and stable diseases) correlated with elevated expression of both topoisomerases by immunohistochemistry in four of six epithelial ovarian or tubal cancer tumor samples. Doxil with 14-day topotecan infusion is a well-tolerated regimen and suitable for study in platinum-resistant or refractory ovarian or tubal cancers. Frequent gastrointestinal toxicity and/or erratic absorption complicate treatment with a longer topotecan infusion or with oral topotecan, respectively, and these combinations are not recommended.